Analytical modeling of threshold voltage of ion-implanted strained-Si-on-Insulator (SSOI) MOSFETs - Rawat G.; Goel E.; Kumar S.; Kumar M.; Dubey S.; Jit S. (My University, 2025)
The purpose of this paper is to present an analytical surface potential based threshold voltage model of ion-implanted fully-depleted (FD) short-channel strained-Si-on-Insulator (SSOI) MOSFETs using parabolic approximation method. We have studied the impact of strain, strained-Si film thickness, channel length and other device parameters on the threshold voltage model. Further, the effect of gate-oxide thickness on Drain Induced Barrier Lowering (DIBL) is also studied. The analytical results are validated by comparison with numerical simulation data extracted from ATLAS™, a two dimensional (2D) device simulator. The proposed model predicts the device characteristics in the subthreshold regime of operation accurately. It can be noted that the channel barrier and threshold voltage are the functions of both device dimensions as well as doping profile parameters like straggle and peak doping position. Copyright © 2014 American Scientific Publishers. All rights reserved.